Foliar Zinc Application on Yield and Quality Characters of Soybean - AYTAC, SELIM; CIRAK, CUNEYT; OZCELIK, HUSEYIN (Asian Journal of Chemistry, 2010)
Present study was conducted to determine the effects of foliar application at different doses of Zn (0, 1500, 3000 and 4500 g ha-1) on yield and some quality characters of soybean in the silty clay soils with high nutrient contents from experimental area of Black Sea Agricultural Research Institute, Turkey using A-3127 and A-3935 soybean cultivars during two consecutive years. Experimental design was a randomized complete block in split plot arrangement with three replications, utilizing cultivars as main plot and zinc rates as subplots. Results from both years indicate that successive zinc rates resulted in a significant increase in oil and protein contents of seed and oil yield. The successive doses of Zn also produced higher seed yield.